Challenges faced by Iz’lah organization in minimizing marriage and family ‘URF in Gombe, Nigeria - Aishatu, Abubakar Kumo; Haneef, Sayed Sikandar Shah; Zakariyah, Luqman (Science Publishing Corporation, RAK Free Trade Zone(UAE), 2018)
Jam‟atu Iz‟latil Bid‟ah wa Iq‟matis Sunnah is a non-governmental Islamic organization working towards the reformation of the Muslim Ummah in compliance with the dictates of Islam. Since its inception in 1980s, Izᾱlah has been conducting da‟awa among Muslims as well as non-Muslims. Among its activities is eliminating some of the contradictory customary practices with the dictates of Islam in marriage and family life. Izalah has made some achievements in its efforts. However, there are some challenges that hinder the achievement of its objectives. This study, therefore, aims at assessing the factors that hinder the success of Izalah in minimizing adherence to marriage and family contradictory customs with Islam in Gombe metropolis of Northern Nigeria. This study through a qualitative interview, surveyed the Izalah affiliates and non-affiliates in this aspect. The result found that there are several reasons causing the hitch. Some emanating from the organization itself, and others from the Muslim community which prose as hurdles in the path of social transformation which the Izalah intends to achieve. These includes misapplication of divorce, absence of strong Islamic values, limited human resources capacity, limited communication skills and Modernity. At the end, the study suggest some recommendations to Izalah and the Muslim community in order to minimize some of these obstacles